CHRONIC PSYCHOLOGICAL STRESS AS A MODULATOR OF INTESTINAL MUCOSAL IMMUNITY - Darwish, Lena (My University, 2024)
Crohn’s disease (CD) is an inflammatory bowel disease driven by genetic, environmental, and microbial factors. CD presents a pressing health concern in Canada which has one of the highest prevalence and incidence rates of CD in the world. Chronic psychological stress has been reported as an environmental risk factor for CD which can provoke flares after a period of quiescence and/or exacerbate inflammation. However, the mechanisms which underpin the relationship between stress and disease activity are not known. Previous work has shown that stress can exacerbate CD by disrupting the gut microbiome, leading to uncontrolled inflammation and dysbiosis. The hypothesis of my work is that chronic psychological stress is a maladaptive immunomodulator of the gut, compromising host interactions with the microbiota and thereby resulting in disease-state dysbiosis. I used a chronic variable stress (CVS) mouse model of chronic stress to probe the effects that stress has on host control of the microbiome as it relates to CD. In this model, I found that while CVS did not modify the structural integrity of the ileum nor the quantities of suspected leukocyte populations, CVS-exposed mice showed a transcriptional profile consistent with Th17 inflammatory activation. Moreover, sequencing of the ileal microbiome showed that CVS may be permissive for expansion of bacterial families originally present in low levels whilst contracting dominant families such as Muribaculaceae and Lactobacillaceae. Dysbiosis was also indicated by a significant increase in stool content of antimicrobial Lipocalin-2 (LCN2). This work will provide valuable insights into the risk factors which drive disease activity, thus informing the standard of care for CD.
Keywords: Crohn's disease, Gut-brain axis, mucosal immunology, AIEC, gastrointestinal, microbiome, immunology